2021
DOI: 10.1051/e3sconf/202126801054
|View full text |Cite
|
Sign up to set email alerts
|

Research on exhaust emission characteristics and technical route under CLTC cycle

Abstract: In this paper, the light duty that meets the China 6 emission standard is selected to study the emission characteristics of different emission control technology routes under China light-duty vehicle test cycle (CLTC). The results show that the cold start stage of CLTC cycle is still the stage with the most pollutant emissions. The THC, CO and NOx emissions of vehicles on the supercharged direct injection technology are higher than those on the naturally aspirated port fuel injection technology. In terms of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Wang et al (2020b) found that fuel consumption between WLTC and RDE was at the same level, while the fuel consumption of CLTC-P was 8.41% higher than that of WLTC. Some studies (Geng et al 2021;Ma et al 2021;Yang et al 2021) also have investigated the emission characteristics of different emission control technology routes under the CLTC-P. However, there is still a lack of a large number of test research on CLTC-P, and a uni ed method for quantitatively evaluating CO 2 emissions measured under different test cycles is yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2020b) found that fuel consumption between WLTC and RDE was at the same level, while the fuel consumption of CLTC-P was 8.41% higher than that of WLTC. Some studies (Geng et al 2021;Ma et al 2021;Yang et al 2021) also have investigated the emission characteristics of different emission control technology routes under the CLTC-P. However, there is still a lack of a large number of test research on CLTC-P, and a uni ed method for quantitatively evaluating CO 2 emissions measured under different test cycles is yet to be established.…”
Section: Introductionmentioning
confidence: 99%